Elementary. Blood and ink - Christopher, Adam, 1978- (Titan Books, 2016)
"The Chief Financial Officer of a secretive NYC hedge fund has been found murdered--stabbed through the eye with an expensive fountain pen. When Sherlock Holmes and Joan Watson discover a link between the victim and an charismatic management guru with a doubtful past, it seems they may have their man. But is the guru being framed? As secrets are revealed and another victim is found murdered in the same grisly fashion, Holmes and Watson begin to uncover a murky world of money and deceit..."--Back cover.